2002
DOI: 10.1086/338886
|View full text |Cite
|
Sign up to set email alerts
|

ChandraDetection of a Type II Quasar atz= 3.288

Abstract: 1 Some of the data presented herein were obtained at the W.M. Keck Observatory, which is operated as a scientific partnership among the CaliforniaWe report on observations of a Type II quasar at redshift z = 3.288, identified as a hard X-ray source in a 185 ks observation with the Chandra X-ray Observatory and as a high-redshift photometric candidate from deep, multiband optical imaging. CXO J084837.9+445352 (hereinafter CXO52) shows an unusually hard X-ray spectrum from which we infer an absorbing column dens… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
146
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(159 citation statements)
references
References 99 publications
13
146
0
Order By: Relevance
“…Moreover, deep ($170 ks) Chandra X-Ray Observatory ACIS imaging of LALA z % 4:5 candidates in both Boötes ( Malhotra et al 2003) and in Cetus ( Wang et al 2004) resulted in X-ray nondetections to an average 3 limiting luminosity of L 2Y8keV < 2:8 ; 10 42 ergs s À1 . This limit is roughly an order of magnitude fainter than what is typically observed for even the heavily obscured, type II AGNs (e.g., Stern et al 2002;Norman et al 2002;Dawson et al 2003). By comparing the upper limit on the typical X-rayYtoYLy luminosity ratio for the Ly galaxy sample to the observed values of this ratio for quasar and Seyfert galaxy samples, Malhotra et al (2003) and Wang et al (2004) concluded that AGNs account for P5% of the Ly galaxy sample.…”
Section: The Equivalent-width Distributionmentioning
confidence: 84%
“…Moreover, deep ($170 ks) Chandra X-Ray Observatory ACIS imaging of LALA z % 4:5 candidates in both Boötes ( Malhotra et al 2003) and in Cetus ( Wang et al 2004) resulted in X-ray nondetections to an average 3 limiting luminosity of L 2Y8keV < 2:8 ; 10 42 ergs s À1 . This limit is roughly an order of magnitude fainter than what is typically observed for even the heavily obscured, type II AGNs (e.g., Stern et al 2002;Norman et al 2002;Dawson et al 2003). By comparing the upper limit on the typical X-rayYtoYLy luminosity ratio for the Ly galaxy sample to the observed values of this ratio for quasar and Seyfert galaxy samples, Malhotra et al (2003) and Wang et al (2004) concluded that AGNs account for P5% of the Ly galaxy sample.…”
Section: The Equivalent-width Distributionmentioning
confidence: 84%
“…Work of this type is discussed in Evans (1998), Vernet et al (2001), Stern et al (1999), Rottgering et al (1997), Stern et al (2002) and Norman et al (2002). Out of these references we found 11 objects that were considered appropriate to investigate the…”
Section: Comparison With Earlier Type-ii Samplesmentioning
confidence: 95%
“…There are a handful of notable exceptions (see Stern et al 2002;Norman et al 2002) but, so far, the numbers were far from enough to make a detailed study of the population. Almost the only way to cure this deficiency is to combine X-ray fluxes and follow-up spectroscopy in X-ray selected samples.…”
Section: Much Of the Uncertainty In Deriving The L([o Iii] λ5007) Lfmentioning
confidence: 99%
“…Four objects are characterized by a high X-ray luminosity (L X ½0:5Y 10 keV > 10 44 ergs s À1 ) and substantial absorption (N H > 10 22 cm À2 ) and we can therefore classify them as type 2 QSOs. Radio-loud type 2 QSOs are known since long times thanks to radio surveys (see McCarthy 1993 for a comprehensive review), while radio-quiet type 2 QSOs have been observed only recently in Chandra and XMM-Newton X-ray surveys (Dawson et al 2001;Norman et al 2002;Mainieri et al 2002;Stern et al 2002;Della Ceca et al 2003;Fiore et al 2003;Tozzi et al 2006) and optical surveys (SDSS; Zakamska et al 2005). Two of our type 2 QSOs candidates, xid ¼ 70 and 2289, are clearly detected in the radio at 20 cm using the Very Large Array ( VLA) with an integrated flux of 540 AE 24 and 52 AE 11 Jy, respectively (Schinnerer et al 2007).…”
Section: Type 2 Qso Candidatesmentioning
confidence: 99%